AN ANALYTICAL STUDY OF DOMESTIC VIOLENCE AGAINST MARRIED WOMEN IN WASHIM DISTRICTS (International Journal of Food and Nutritional Sciences, 2022)
If you look at any newspaper, you will come across many incidents like bride abuse for hoodia. There are many cases like this that are devoid of Nand. Many such cases are happening continuously in our country. Some are being tortured, some are being beaten and some are being killed. This is true in all places and for people of all ages, rural, tribal, and urban areas are no exception. Violence is passed down from one generation to another. The term used to describe this divisive problem of domestic violence is domestic violence. Any member of the family can be a victim of domestic violence, be it a wife, husband, son, daughter, or mother. It can be parents, grandparents, etc. But this research essay focuses on violence against women. Violence can take various forms such as physical, sexual, or emotional. If we look at the society we live in from a sociological perspective, domestic violence has become an integral part of society. Various situations also add to the intensity of psychological problems and social influences. The severity of violence may vary by geographic location and cultural differences. The functions of their domestic incidents have been analyzed.